2007
DOI: 10.1902/jop.2007.060136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Period After Ovariectomy on Femoral and Mandibular Bone Density and on Induced Periodontal Disease

Abstract: The period influenced the femoral BMD and the vertical bone loss in induced periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
2
9
0
2
Order By: Relevance
“…The proximal tibia is more sensitive to the effects of estrogen deficiency than the jaw bones, since less bone area was observed as soon as 60 days after OVX. This result is in agreement with other authors who compared jaw bones and long bones [6,8,28,35,38,39]. Liu et al [37] studied the influence of ovariectomy in rats, by micro-CT, in several bones and observation periods between 0 and 36 weeks, and found significant difference in tibia BV/TV as soon as 4 weeks.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The proximal tibia is more sensitive to the effects of estrogen deficiency than the jaw bones, since less bone area was observed as soon as 60 days after OVX. This result is in agreement with other authors who compared jaw bones and long bones [6,8,28,35,38,39]. Liu et al [37] studied the influence of ovariectomy in rats, by micro-CT, in several bones and observation periods between 0 and 36 weeks, and found significant difference in tibia BV/TV as soon as 4 weeks.…”
Section: Discussionsupporting
confidence: 90%
“…According to several authors [28], estrogen deficiency did not promote maxillary osteoporosis in rats even 11 weeks after ovariectomy. After 51 or 150 days, Orrico et al [39] found no difference between OVX and SHAM groups with regard to mandibular bone mineral density. Although we analyzed alveolar bone in the mandible and maxilla, we used different regions to those analyzed by other authors [4,35,36], who evaluated larger areas at lower magnifications.…”
Section: Discussionmentioning
confidence: 96%
“…Since both osteoporosis and periodontitis are highly prevalent and markedly associated with aging, studies have been performed to investigate the association between these diseases over the past decades [39, 40, 42]. Experimental results [43] suggest that despite those studies, no clear association between these diseases exist other than common risk factors. Through recognizing common risk factors for both osteoporosis and periodontal disease and performing clinical and radiographic dental examinations dentists identify patients who are at risk of developing osteoporosis.…”
Section: Oral Health In Patients With Osteoporosismentioning
confidence: 99%
“…For example, bone mineral density in relationship to periodontal condition was examined in older or postmenopausal women in a number of studies (20,21). In animal experiments, rats and mice were subjected to ovariectomy procedures and studied, as osteopenic animal models are known to mimic the development of estrogen deficiency-induced osteopenia in humans (56). However, despite those various studies, no clear linkage between these diseases has been shown.…”
Section: Osteoporosismentioning
confidence: 99%